Análise da composição química, da atividade biológica e da quimiossistemática dos óleos essenciais em Eugenia (Myrtaceae) - Silveira, Raisa Maria (2023)
Myrtaceae is a pantropical family with approximately 132 genera and 5760 species. In the family, essential oils are widely produced by their representatives, to the point that the presence of their secretory structures is used in taxonomic identification. This is the case of Eugenia species, the largest neotropical genus of Myrtaceae, comprising more than 1000 species. Essential oils originate from the secondary metabolism of plants and obtained from plants or their parts, extracted through distillation processes. The objective of this project is to determine the phytochemical and environmental patterns of essential oils from Eugenia species, the use of essential oils as chemosystematic markers, the influence of seasonality on the chemical composition of these oils and to evaluate the anxiolytic activities and toxicity of essential oils in the body. model. The compilation of data on the chemical composition of the essential oils available in the literature was carried out, as well as the collection, extraction and identification of the chemical composition of the essential oils from the collected specimens. Then, several statistical analyzes were carried out to determine the phytochemical and environmental patterns of the essential oils of Eugenia species and the influence of seasonality on the chemical composition of these oils (factor analysis, regression analysis, multivariate analysis of variance and meta-analysis). The results were that: a) essential oils are chemosystematic characters that help in the infrageneric circumscription and corroborate phylogenetic hypotheses of the genus; b) the phytochemical profile in relation to the volatile composition of Eugenia species was determined, being significantly different between species; c) the chemical composition of essential oils were significantly different between seasons; and d) the essential oils showed anxiolytic activity in tests with zebrafish.